Intra-annual variations of spectrally resolved gravity wave activity in the upper mesosphere/lower thermosphere (UMLT) region - R. Sedlak; A. Zuhr; C. Schmidt; S. Wüst; M. Bittner; G. G. Didebulidze; C. Price (Atmospheric Measurement Techniques, 2020)
The period range between 6 and 480 min is known to represent the major part of the gravity wave spectrum driving mesospheric dynamics. We present a method using wavelet analysis to calculate gravity wave activity with a high period resolution and apply it to temperature data acquired with the OH* airglow spectrometers called GRIPS (GRound-based Infrared P-branch Spectrometer) within the framework of the NDMC (Network for the Detection of Mesospheric Change; https://ndmc.dlr.de , last access: 22 September 2020). We analyse data measured at the NDMC sites Abastumani in Georgia (ABA; 41.75 ∘ N, 42.82 ∘ E), ALOMAR (Arctic Lidar Observatory for Middle Atmosphere Research) in Norway (ALR; 69.28 ∘ N, 16.01 ∘ E), Neumayer Station III in the Antarctic (NEU; 70.67 ∘ S, 8.27 ∘ W), Observatoire de Haute-Provence in France (OHP; 43.93 ∘ N, 5.71 ∘ E), Oberpfaffenhofen in Germany (OPN; 48.09 ∘ N, 11.28 ∘ E), Sonnblick in Austria (SBO; 47.05 ∘ N, 12.95 ∘ E), Tel Aviv in Israel (TAV; 32.11 ∘ N, 34.80 ∘ E), and the Environmental Research Station Schneefernerhaus on top of Zugspitze mountain in Germany (UFS; 47.42 ∘ N, 10.98 ∘ E). All eight instruments are identical in construction and deliver consistent and comparable data sets. For periods shorter than 60 min, gravity wave activity is found to be relatively low and hardly shows any seasonal variability on the timescale of months. We find a semi-annual cycle with maxima during winter and summer for gravity waves with periods longer than 60 min, which gradually develops into an annual cycle with a winter maximum for longer periods. The transition from a semi-annual pattern to a primarily annual pattern starts around a gravity wave period of 200 min. Although there are indications of enhanced gravity wave sources above mountainous terrain, the overall pattern of gravity wave activity does not differ significantly for the abovementioned observation sites. Thus, large-scale mechanisms such as stratospheric wind filtering seem to dominate the evolution of mesospheric gravity wave ...